Optimalisasi Penggunaan Energi Listrik Pada Fakultas Teknik Universitas Serambi Mekkah Menggunakan Metode Genetik Algoritma - Samsuddin Samsuddin; T.M Azis Pandria; Munawir Munawir (Jurnal Serambi Engineering, 2019)
Ideally the increase in electrical energy needs is proportional to the supply, but these conditions often cannot be met by the energy provider. This condition can affect the quality of electrical energy supply to customers, such as system outages to power outages. Short-term solutions and concrete steps in an effort to overcome these problems is saving electricity usage. In accordance with presidential regulation no. 5 of 2006 concerning energy conversion and the decision of the Minister of National Education No. 13 of 2012 about Savings on the Use of Electric Energy in government and private institutions, it is necessary to make efficient use of electricity in the University Of Serambi Mekkah Faculty of Engineering. There is no data on energy consumption in the building. It is necessary to conduct an energy audit of the building to determine the level of energy use in the building. The initial IKE value is a guideline for decision making whether or not a detailed audit is needed for the building. The audit results are Energy Saving Opportunities (PHE) that can be obtained by applying the optimal Energy Consumption Intensity (IKE). The results obtained energy savings reached 45.65% from the initial data.